HTLV-1 bZIP factor induces T-cell lymphoma and systemic inflammation in vivo. - Yorifumi Satou; Jun-Ichirou Yasunaga; Tiejun Zhao; Mika Yoshida; Paola Miyazato; Ken Takai; Kei Shimizu; Koichi Ohshima; Patrick L Green; Naganari Ohkura; Tomoyuki Yamaguchi; Masahiro Ono; et al. (PLoS Pathogens)
Human T-cell leukemia virus type 1 (HTLV-1) is the causal agent of a neoplastic disease of CD4+ T cells, adult T-cell leukemia (ATL), and inflammatory diseases including HTLV-1 associated myelopathy/tropical spastic paraparesis, dermatitis, and inflammatory lung diseases. ATL cells, which constitutively express CD25, resemble CD25+CD4+ regulatory T cells (T(reg)). Approximately 60% of ATL cases indeed harbor leukemic cells that express FoxP3, a key transcription factor for T(reg) cells. HTLV-1 encodes an antisense transcript, HTLV-1 bZIP factor (HBZ), which is expressed in all ATL cases. In this study, we show that transgenic expression of HBZ in CD4+ T cells induced T-cell lymphomas and systemic inflammation in mice, resembling diseases observed in HTLV-1 infected individuals. In HBZ-transgenic mice, CD4+Foxp3+ T(reg) cells and effector/memory CD4+ T cells increased in vivo. As a mechanism of increased T(reg) cells, HBZ expression directly induced Foxp3 gene transcription in T cells. The increased CD4+Foxp3+ T(reg) cells in HBZ transgenic mice were functionally impaired while their proliferation was enhanced. HBZ could physically interact with Foxp3 and NFAT, thereby impairing the suppressive function of T(reg) cells. Thus, the expression of HBZ in CD4+ T cells is a key mechanism of HTLV-1-induced neoplastic and inflammatory diseases.